Thermal And Optical Properties Of High Power Infrared Emitter Utilizing Transient Dual Interface Method - Ching, Chin Peng (2013)
High power IR emitters are new emerging technology in solid state lighting market. Since thermal problem is becoming more crucial and is believed to be directly responsible for their limited performance and failures, this master research aims to study thermal behavior as well as optical properties of the high power IR emitters in terms of chip and package levels. A total of eight experiments have been performed to enhance a better understanding on the optimum operating conditions and also to identify factors that would affect the thermal performance of the IR packages. It was found that thermal resistances varied as a function of input current and ambient temperature. Besides, measurement carried out on a cold-plate offered much lower total thermal resistance RthJA, 5.24 K/W compared to that performed in an oven, 35.5 K/W. In addition, it was essential to consider optical power in the evaluation of structure functions to obtain accurate real thermal resistances of the IR emitters since the electrical junction-to-board thermal resistance RthJB obtained without optical power consideration was 35.2% lower than its real value. By utilizing transient dual interface method, the exact point of separation between the IR package and external heat sink, i.e., MCPCB or cold-plate could be precisely determined. As a result, real junction-to-case thermal resistance RthJC and junction-to-board thermal resistance RthJB were 4.62 ± 0.05 K/W and 10.15 ± 0.05 K/W respectively.